High Temperature Fast Field Cycling Study of Crude Oil - Lozovoi, Artur; Hurlimann, Martin; Kausik, Ravinath; Stapf, Siegfried; Mattea, Carlos (Diffusion Fundamentals, 2017)
A set of crude oil samples with different composition and characteristics is studied by means of Fast Field Cycling (FFC) 1H relaxometry, which probes the distribution of longitudinal relaxation times T1 as a function of the Larmor frequency. Investigation of T1 profiles at different temperatures is able to provide an insight into the dynamics and structural changes of oil components, with our particular interest being the high temperature behaviour of asphaltene. It is well-known that asphaltenes tend to form porous clusters in crude oils, which can cause severe problems for the process of oil extraction. Therefore, FFC experiments are conducted on Stelar Spinmaster FFC2000 in the temperature range 203K < T <443K, where the upper limit of 443K is aimed at approximating the typical maximal in-situ well temperatures. FFC relaxometry data of crude oils at such a high temperature are obtained for the first time with the use of a specially modified NMR probe. Inverse Laplace transformation is applied to the longitudinal agnetization decays, yielding T1 distributions at different frequencies. A comparative analysis of these distributions for different Larmor frequencies and temperatures showed that there is a systematic variation of the frequency dependence of T1 correlating with the asphaltene content in the samples, at temperatures similar to the well conditions.